Performance of Dynamic Voltage Restorer by Using Fuzzy Controller With Battery Energy Storage System (International Journal of Engineering and Computer Science, 2015)
Inthis paper the dynamic Voltage Restorer (DVR) has as of late been acquainted with shield the touchy mechanical burdens from the impeding impacts of voltage lists/swells and other voltage aggravations. Different injection schemes for DVR are analyzed with particular focus on new method used to minimize the rating of voltage source converter(VSC) used in DVR. Anew control technique is proposed to control the capacitor-supported DVR. The control of DVR is demonstrated with a reduced-rating VSC. The reference load voltage is estimated using the unit vectors. The synchronous reference frame theory is used for the conversion of voltages from rotating vectors to the stationary frame. In this control scheme fuzzy logic controller is used to activate the Pulse Width Converter.  The compensation of the voltage sag,swell and hormonics is demonstrated using a reduced-rating DVR.Results shows that this method can compensate voltage sag, swell and harmonics.